Suffering Experiences of Girl Students Against Sexual Harassment (Surkhet Journal, 2014)
Sexual harassment is a global issue and commonly experienced by girls and women around the world. This paper attempts to explore the suffering experiences of girl students against sexual harassment using primary data from girl students of Surkhet Campus (Education). It focuses qualitative as well as exploratory research design where Focus Group Discussion was applied for the collection of qualitative data. Purposive sampling procedure was adopted for selecting informants. It was found that most of the respondents had heard the term of sexual harassment; but were not clear about its meaning. This showed that most of the respondents had low level of understanding regarding the topic. Sexual harassment was widely experienced by girl students in their college. The most common form of sexual harassment came across the use of absence language in classrooms and the college compound. Most of the FGD participants in all levels said that boys tease and they say “I love you”, and bad words such as sexy (chwank), lovely, big buttock, etc. are used to address. Boys tease girls’ and attempts touching their body and private parts. Most of the girls said that they were harassed in classroom specially in the absence of the teachers. Majority of them reported that their own boyfriends or boy students are the main perpetrators of sexual harassment. Most of them reported that sexual harassment has a negative impact on their study. Seventeen girls among 23, participated in FGDs reported that because of sexual harassment in their college, they faced the psychological problems. All the girls participating in M. Ed. level have overwhelmingly voiced on the necessity of sex education in college. They wished for effective laws to punish the Perpetrator. Most of them also suggested perpetrators must apologize with written commitment, they have to be changed or suspended temporarily from the college. Few of them suggested perpetrators must be expelled permanently from college.